Turkish Mathematics and Science Teachers' Technology Use in Their Classroom Instruction: Findings from TIMSS 2011 - Yasemin Tas; Esra Balgalmis (Seyit Ahmet Kıray, 2016)
The goal of this study was to describe Turkish mathematics and science teachers' use of computer in their classroom instruction by utilizing TIMSS 2011 data. Analyses results revealed that teachers most frequently used computers for preparation purpose and least frequently used computers for administration. There was no difference in teachers' technology usage ways in regard to gender. Although teachers had ready access to computer staff in their schools for technical problems and received adequate support for integrating computers in their teaching activities, teachers used computer software rarely as basis for instruction. Textbook was the most commonly used resource as the basis for instruction. In 69.6% of the mathematics classes and in 41.5% of the science classes, students had computer(s) available to use during lessons and in computer available classes, computers were generally connected to internet. Students rarely engaged in computer activities, such as exploring principles and concepts, practicing skills and procedures, looking up ideas and information, doing experiments, processing and analyzing data. Suggestions were made in order to improve technology usage in mathematics and science instruction.